1987
DOI: 10.1111/j.1525-1470.1987.tb00756.x
|View full text |Cite
|
Sign up to set email alerts
|

Kawasaki Disease and its Diagnosis

Abstract: Mucocutaneous lymph node syndrome, or Kawasaki disease, is a febrile, exanthematous disease of children that has potentially fatal complications. The most important complication is the development of aneurysms in the coronary arteries, which may thrombose or occasionally, rupture and cause severe morbidity or death. Criteria for the diagnosis of Kawasaki disease have been developed that may help the clinician make the diagnosis and prevent complications. The major criteria include fever, skin eruption, ocular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Thrombocytosis is a characteristic, though nonspecific, feature of KD [1][2][3]. However, Hara et al [7] noted thrombocytopenia in 10 of 486 patients with KD (2%), and Niwa et al [13] found 10 such cases out of 303 affected young children (3.3%).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Thrombocytosis is a characteristic, though nonspecific, feature of KD [1][2][3]. However, Hara et al [7] noted thrombocytopenia in 10 of 486 patients with KD (2%), and Niwa et al [13] found 10 such cases out of 303 affected young children (3.3%).…”
Section: Discussionmentioning
confidence: 97%
“…The diagnosis is supported by laboratory findings of thrombocytosis and elevated erythrocyte sedimentation rate. According to some authors, thrombocytosis develops in virtually all patients with KD [2]. However, a minority of KD patients (1-2%) may exhibit a significant decrease in platelet count [3].…”
mentioning
confidence: 99%
“…19-6A), oral mucosal erythema (Fig. 74 Anterior uveitis has also been noted in many patients with this disorder. 74 Anterior uveitis has also been noted in many patients with this disorder.…”
Section: Anterior Segment Ischemiamentioning
confidence: 93%
“…The differential diagnosis of Kawasaki disease includes toxic shock syndrome, scarlet fever, staphylococcal scalded skin syndrome, erythema multiforme, drug allergy, and collagen‐vascular disease. Criteria have been developed to establish the diagnosis [76]. No specific form of treatment is available, but early aspirin [77] and intravenous gamma globulin [78] therapy may reduce complications.…”
Section: Kawasaki Disease or Acute Febrile Mucocutaneous Lymph Node Smentioning
confidence: 99%